Cervical Intraepithelial Neoplasia grade 2 biopsy: Do p16INK4a and Ki-67 biomarkers contribute to the decision to treat? A cross-sectional study - Ferreira, Amanda Leal; Dibe, Nasle Domingues; Paiva, Bruna Rodrigues de; Portari, Elyzabeth Avvad; Dock, Dione Corrêa de Araújo; Ferreira, Nilma Valéria Caldeira; Gomes Junior, Saint Clair; Russomano, Fábio Bastos; Andrade, Cecília Vianna de (São Paulo Medical Journal, 2025)
BACKGROUND: Managing cervical intraepithelial neoplasia grade 2 (CIN2) is challenging, considering the CIN2 regression rate, perinatal risks associated with excisional procedures, and insufficient well-established risk factors to predict progression. OBJECTIVES: To determine the ability of p16INK4a and Ki-67 staining in biopsies diagnosed with CIN2 to identify patients with higher-grade lesions (CIN3 or carcinoma). DESIGN AND SETTING: Cross-sectional study conducted at a referral center for treating uterine cervical lesions. METHODS: In 79 women, we analyzed the correlation of p16INK4a and Ki-67 expression in CIN2 biopsies with the presence of a higher-grade lesions, as determined via histopathology in surgical specimens from treated women or via two colposcopies and two cytological tests during follow-up for untreated women with at least a 6-month interval. The expression of these two biomarkers was verified by at least two independent pathologists and quantified using digital algorithms. RESULTS: Thirteen (16.8%) women with CIN2 biopsy exhibited higher-grade lesions on the surgical excision specimen or during follow-up. p16INK4a expression positively and negatively predicted the presence of higher-grade lesions in 17.19% and 86.67% patients, respectively. Ki-67 expression positively and negatively predicted the presence of higher-grade lesions in 40% and 88.24% patients, respectively. CONCLUSIONS: Negative p16INK4a and Ki67 immunohistochemical staining can assure absence of a higher-grade lesion in more than 85% of patients with CIN2 biopsies and can be used to prevent overtreatment of these patients. Positive IHC staining for p16INK4a and Ki-67 did not predict CIN3 in patients with CIN2 biopsies.